Flight morphology corresponds to both surrounding landscape structure and local patch conditions in a highly specialized peatland butterfly (Lycaena epixanthe). (6th June 2018) - Crawford, Lindsay A.; Keyghobadi, Nusha
Abstract : 1. Movement mediates the response of populations and communities to landscape and habitat spatial structure, yet movement capability may itself be modified by selection pressures accompanying landscape change. Insect flight morphology can be affected by both the landscape surrounding habitat patches and the distribution of resources within habitat patches. 2. This study investigated the relative influence of local habitat patch conditions and surrounding landscape structure on variation in morphological traits associated with flight in the bog copper ( Lycaena epixanthe ), a butterfly endemic to temperate Nearctic peatlands. 3. Eight habitat patches were sampled to assess the influence of the surrounding landscape (connectivity of potential habitat and matrix composition) and patch size (an integrated proxy of resource density and spatial distribution) on investment into flight, measured by thorax and abdomen mass, and wing area. 4. The results revealed an effect of both local habitat conditions and landscape structure on flight‐related morphological traits. Increasing forest cover in the surrounding landscape, indicative of increased habitat patch isolation, corresponded with less mobile phenotypes in both sexes. Surrounding landscapes with more water were also generally associated with less mobile phenotypes. Investment into flight was greater in smaller peatlands in which host plant density is higher and more homogeneously distributed. 5. The present study highlights that morphological traits associated with mobility may be responding to both local habitat patch characteristics and surrounding landscape structure. It also supports the hypothesis that local habitat conditions contribute to morphological variation in butterflies. Abstract : Increasing forest cover in the surrounding landscape, indicative of increased habitat patch isolation, corresponded with less mobile phenotypes. Surrounding landscapes with more water were also associated with less mobile phenotypes. Investment into flight was greater in smaller peatlands in which host plant density is higher and more homogeneously distributed. This study highlights that morphological traits associated with mobility may respond not only to surrounding landscape structure but also to local habitat patch conditions.